2004
DOI: 10.1007/s00415-004-0550-9
|View full text |Cite
|
Sign up to set email alerts
|

Neurological abnormalities associated with celiac disease

Abstract: If this association is not coincidental, both the central and the peripheral nervous systems may be affected in CD by a spectrum of neurological disorders that are either the outcome of CD or share the same pathogenesis with the enteropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 29 publications
0
48
0
5
Order By: Relevance
“…As described in this section, it is well-established that the anticholinergic effects of first and second generation antipsychotics, and clozapine in particular, contribute to and compound GI motility issues such as constipation and bowel obstruction. Interestingly, while there exists substantial GI comorbidities in schizophrenia, the reverse may also be true, as increasingly psychiatric comorbidities are being reported in individuals with GI disorders such as irritable bowel syndrome (IBS), inflammatory bowel disease (IBD) and celiac disease [36][37][38][39][40]. In this section, we review the motility effects of psychiatric medications, appraise current information regarding GI inflammation in schizophrenia as an inherent disease pathology and examine the overlapping epidemiology of the autoimmune disorder, celiac disease, and other dietary-based sensitivities with schizophrenia.…”
Section: Gi Issues For Consideration By Psychiatric Cliniciansmentioning
confidence: 99%
“…As described in this section, it is well-established that the anticholinergic effects of first and second generation antipsychotics, and clozapine in particular, contribute to and compound GI motility issues such as constipation and bowel obstruction. Interestingly, while there exists substantial GI comorbidities in schizophrenia, the reverse may also be true, as increasingly psychiatric comorbidities are being reported in individuals with GI disorders such as irritable bowel syndrome (IBS), inflammatory bowel disease (IBD) and celiac disease [36][37][38][39][40]. In this section, we review the motility effects of psychiatric medications, appraise current information regarding GI inflammation in schizophrenia as an inherent disease pathology and examine the overlapping epidemiology of the autoimmune disorder, celiac disease, and other dietary-based sensitivities with schizophrenia.…”
Section: Gi Issues For Consideration By Psychiatric Cliniciansmentioning
confidence: 99%
“…64 Thirdly, shared immunological abnormalities suggest a common underlying vulnerability between active CD and neuropsychiatric disorders. 65,66 It has been postulated that gluten may exert its pathogenic effect on processes in the brain through cell-mediated immune mechanisms and lymphocyte stimulation. 67 Impaired availability of tryptophan and disturbances in central serotonergic function may play a role in the development of anxiety, headaches ⁄ migraines, behavioural symptoms and depression in CD.…”
Section: Ongoing Mucosal Inflammation and Injurymentioning
confidence: 99%
“…[51] One small, retrospective study found a broad spectrum of these neurological disorders in 12 % of 148 pediatric and adult CD patients. [51] Cognitive decline, dementia, myopathy, and a rarer clinical condition involving epilepsy and cerebral calcifications in relation to CD have been described in case reports and series.…”
Section: Neurological Manifestationsmentioning
confidence: 99%
“…[51] One small, retrospective study found a broad spectrum of these neurological disorders in 12 % of 148 pediatric and adult CD patients. [51] Cognitive decline, dementia, myopathy, and a rarer clinical condition involving epilepsy and cerebral calcifications in relation to CD have been described in case reports and series. [52][53][54][55] Several recent studies have evaluated the prevalence and clinical presentation of ataxia and peripheral neuropathy associated with CD, as well as the potentially gluten-dependent neurological conditions occurring in the absence of enteropathy.…”
Section: Neurological Manifestationsmentioning
confidence: 99%